LST1/A is a myeloid leukocyte-specific transmembrane adaptor protein recruiting protein tyrosine phosphatases SHP-1 and SHP-2 to the plasma membrane - Dráber, Peter; Štěpánek, Ondřej; Hrdinka, M; Drobek, Aleš; Chmatal, Lukas; Mala, Linda; Ormsby, Tereza; Angelisová, Pavla; Hořejší, Václav; Brdička, Tomáš (The Journal of biological chemistry, 2012)
Transmembrane adaptor proteins are membrane-anchored proteins consisting of a short extracellular part, a transmembrane domain, and a cytoplasmic part with various protein-protein interaction motifs but lacking any enzymatic activity. They participate in the regulation of various signaling pathways by recruiting other proteins to the proximity of cellular membranes where the signaling is often initiated and propagated. In this work, we show that LST1/A, an incompletely characterized protein encoded by MHCIII locus, is a palmitoylated transmembrane adaptor protein. It is expressed specifically in leukocytes of the myeloid lineage, where it localizes to the tetraspanin-enriched microdomains. In addition, it binds SHP-1 and SHP-2 phosphatases in a phosphotyrosine-dependent manner, facilitating their recruitment to the plasma membrane. These data suggest a role for LST1/A in negative regulation of signal propagation.
Keywords: HeLa Cells; Pseudopodia; primární buněčná kultura; plakiny; Protein Structure, Tertiary; Protein Tyrosine Phosphatase, Non-Receptor Type 11; Jurkat buňky; tyrosinfosfatasa nereceptorového typu 6; HEK293 Cells; Myeloid Cells; sekvence aminokyselin; U937 Cells; terciární struktura proteinů; lidé; HeLa buňky; Molecular Sequence Data; Protein Transport; hlavní histokompatibilní komplex; signální transdukce; membránové proteiny; Amino Acid Sequence; Major Histocompatibility Complex; Signal Transduction; HEK293 buňky; Protein Tyrosine Phosphatase, Non-Receptor Type 6; transport proteinů; myeloidní buňky; molekulární sekvence - údaje; pseudopodia; Membrane Proteins; U937 buňky; tyrosinfosfatasa nereceptorového typu 11; Jurkat Cells; buněčná membrána; Plakins; Primary Cell Culture; Cell Membrane; Humans